Long-term exposure to PM and all-cause and cause-specific mortality: A systematic review and meta-analysis - Chen, Jie; Hoek, Gerard (Environment international, 2020)
•Long-term exposure to PM2.5 and/or PM10 is associated with increased mortality.•Associations with PM2.5 were more consistent than with PM10.•Associations with PM2.5 remained at low exposure levels. As new scientific evidence on health effects of air pollution is generated, air quality guidelines need to be periodically updated. The objective of this review is to support the derivation of updated guidelines by the World Health Organization (WHO) by performing a systematic review of evidence of associations between long-term exposure to particulate matter with diameter under 2.5 µm (PM2.5) and particulate matter with diameter under 10 µm (PM10), in relation to all-cause and cause-specific mortality. As there is especially uncertainty about the relationship at the low and high end of the exposure range, the review needed to provide an indication of the shape of the concentration–response function (CRF). We systematically searched MEDLINE and EMBASE from database inception to 9 October 2018. Articles were checked for eligibility by two reviewers. We included cohort and case-control studies on outdoor air pollution in human populations using individual level data. In addition to natural-cause mortality, we evaluated mortality from circulatory diseases (ischemic heart disease (IHD) and cerebrovascular disease (stroke) also specifically), respiratory diseases (Chronic Obstructive Pulmonary Disease (COPD) and acute lower respiratory infection (ALRI) also specifically) and lung cancer. A random-effect meta-analysis was performed when at least three studies were available for a specific exposure-outcome pair. Risk of bias was assessed for all included articles using a specifically developed tool coordinated by WHO. Additional analyses were performed to assess consistency across geographic region, explain heterogeneity and explore the shape of the CRF. An adapted GRADE (Grading of Recommendations Assessment, Development and Evaluation) assessment of the body of evidence was made using a specifically developed tool coordinated by WHO. A large number (N = 107) of predominantly cohort studies (N = 104) were included after screening more than 3000 abstracts. Studies were conducted globally with the majority of studies from North America (N = 62) and Europe (N = 25). More studies used PM2.5 (N = 71) as the exposure metric than PM10 (N = 42). PM2.5 was significantly associated with all causes of death evaluated. The combined Risk Ratio (RR) for PM2.5 and natural-cause mortality was 1.08 (95%CI 1.06, 1.09) per 10 µg/m3. Meta analyses of studies conducted at the low mean PM2.5 levels (<25, 20, 15, 12, 10 µg/m3) yielded RRs that were similar or higher compared to the overall RR, consistent with the finding of generally linear or supra-linear CRFs in individual studies. Pooled RRs were almost identical for studies conducted in North America, Europe and Western Pacific region. PM10 was significantly associated with natural-cause and most but not all causes of death. Application of the risk of bias tool showed that few studies were at a high risk of bias in any domain. Application of the adapted GRADE tool resulted in an assessment of “high certainty of evidence” for PM2.5 with all assessed endpoints except for respiratory mortality (moderate). The evidence was rated as less certain for PM10 and cause-specific mortality (“moderate” for circulatory, IHD, COPD and “low” for stroke mortality. Compared to the previous global WHO evaluation, the evidence base has increased substantially. However, studies conducted in low- and middle- income countries (LMICs) are still limited. There is clear evidence that both PM2.5 and PM10 were associated with increased mortality from all causes, cardiovascular disease, respiratory disease and lung cancer. Associations remained below the current WHO guideline exposure level of 10 µg/m3 for PM2.5. Systematic review registration number (PROSPERO ID): CRD42018082577.